2022
DOI: 10.4103/jfmpc.jfmpc_1991_21
|View full text |Cite
|
Sign up to set email alerts
|

Attitude, knowledge, and barriers towards research analysis and writing in Saudi Arabia

Abstract: Background: Conducting research requires the integration of certain levels of practice and knowledge, together with the right attitude. This study aimed to investigate the attitude, knowledge, and barriers regarding research analysis and writing among medical residents in Saudi Arabia Methods: This was an online-based cross-sectional study that was conducted in Saudi Arabia. Our targeted population was Saudi medical residents who were enrolled in the Saudi Commission fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Iqra Nawaz, 1 Jonaviva Anthony Thomas, 2 Prakash Gupta, 3 Duha Shellah, 4 Mihnea-Alexandru Găman, 5 Juan C. Puyana, 6 Francisco J. Bonilla-Escobar. 7 Medical research serves as a pivot upon which the advancement of clinical practice oscillates.…”
Section: Should a Scientific Publication Be A Prerequisite To Graduat...mentioning
confidence: 99%
See 1 more Smart Citation
“…Iqra Nawaz, 1 Jonaviva Anthony Thomas, 2 Prakash Gupta, 3 Duha Shellah, 4 Mihnea-Alexandru Găman, 5 Juan C. Puyana, 6 Francisco J. Bonilla-Escobar. 7 Medical research serves as a pivot upon which the advancement of clinical practice oscillates.…”
Section: Should a Scientific Publication Be A Prerequisite To Graduat...mentioning
confidence: 99%
“…By keeping up with recent advancements, students remain updated about current guidelines and treatment procedures. 3 Furthermore, involvement of medical students in research projects during early years in medical schools is also positively associated with sustained publication after graduation. 4 Also, this undergraduate research experience enhances their inclination towards pursuing an academic medical career and enrolling in prestigious academic programs and specialties.…”
Section: Should a Scientific Publication Be A Prerequisite To Graduat...mentioning
confidence: 99%
“…To keep the research cycle moving, in addition to motivating students in health sectors to do so as well. Evidences suggest that postgraduate medical trainees who participate in adequate research activities have better critical thinking skills, medical supervision, and lifelong learning [3,4]. Since replacing the individualized, unsystematic decisions in clinical practice in 1992, evidence-based medicine has been the accepted approach to patient care.5 Clinical research is the foundation of evidence-based medicine and a key to providing the best possible care for patients [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study conducted in a military hospital in Saudi Arabia found that most of the general practitioners who were included in the study had no research publications and were not working on any research projects, despite the fact that most of them had positive attitudes [3][4][5][6][7][8][9][10]. For example, the field of family medicine is still developing and is a relatively new one in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%